Effect of Ar, O2, and N2 Plasma on the Growth and Composition of Vanadium Oxide Nanostructured Thin Films. Issue 18 (4th July 2018) - Singh, Megha; Kumar, Prabhat; Reddy, Gade Brahmaiah
Abstract: Vanadium oxide nanostructured thin films (NTFs) are synthesized using plasma assisted sublimation process (PASP) in different gases' Ar, O2, and N2 plasma (AP, OP, and NP) and O2 gas (OG) ambient. Morphological studies conducted via electron microscopy reveal nanostrips, nanoflakes, nanorods, and nanoparticles organized as clusters for OP, OG, AP, and NP respectively. X‐ray photoelectron spectroscopy (XPS) studies show that samples OP and OG are composed of α‐V2 O5, whereas AP and NP are composed of V6 O13 along with V2 O5 . The relative percentages calculated using XPS data show that in AP, V6 O13, and V2 O5 are 38 and 62%, respectively. These percentages change to 48% for V6 O13 and 52% for V2 O5 in NP. The V6 O13 /V2 O5 ratio is lower in AP than NP. This increment of V6 O13 in NP is due to presence of more reductive species in N2 plasma than Ar plasma. Since N2 plasma contains species like N*, N 2 −, etc. it leads to the formation of NO2, N2 O, etc. Raman spectra indicate the surface of the sample NP consisting of both V6 O13 and V2 O5, agreeing with the X‐ray diffraction (XRD) and XPS results. Studies demonstrate that plasma ambient during synthesis process affects both morphology and composition of deposited vanadium oxide NTFs. Abstract : Potential of materials in the field of research and development provides a powerful impetus which drives scientists toward research in vanadium oxides(V x O y ). The V x O y films deposit in different plasma ambients (O2, N2, Ar), resulting in films with stoichiometry ratio ≤2.5. The plasma ambient plays an essential role in determining the properties of vanadium oxide films.